Relationships between changes in uric acid parameters metabolism and parameters of immunity and microbiota in patients with neuroendocrine-immune complex dysfunction - Gozhenko, Anatoliy; Smagliy, Vadym; Korda, Inna; Badiuk, Nataliya; Zukow, Walery; Kovbasnyuk, Marta; Popovych, Igor (Journal of Education, Health and Sport, 2020)
Background. Previously by screening correlation links between uricemia and uricosuria, on the one hand, and immunity and microbiota parameters, on the other, registered in patients with chronic pyelonephritis and cholecystitis in remission twice (before and after ten days of balneotherapy), we found that raw uricemia determines by 28% nine parameters of immunity as well as bacteriuria and content in E. coli feces. Uricemia, normalized by sex and age, determines by 25% another constellation of immunity parameters as well as content in E. coli feces with impaired enzymatic activity and Klebsiela&Proteus. Instead, uricosuria determines only four parameters of immunity and only by 11,5%. The purpose of this study is to analyze the correlation between individual changes in the two parameter sets caused by balneotherapy. Material and Methods. The object of observation were 34 men and 10 women aged 24-70 years old, who came to the Truskavets’ spa for the rehabilitation treatment of chronic pyelonephritis combined with cholecystitis in remission. The serum and daily urine levels of the uric acid by uricase method were determined. Immune status evaluated on a set of I and II levels recommended by the WHO. The condition of microbiota is evaluated on the results of sowing of feces and urine. Results. It is found that individual changes in uricemia correlate inversely with changes in the level of T-helpers in blood as well as IgA and IgS in saliva while positively with changes in the level of Monocytes with the almost same force as their static levels. Instead, inverse links with changes in inflammatory markers and positive connections with changes in CIC and T-killers that are absent with respect to static parameters are revealed. However, no association was found between changes in uricemia and the intensity of Staph. aureus phagocytosis by blood neutrophils. Changes in uricosuria correlate with changes in only three immune parameters, and even at the limit of significance. Taking into account other relationships, we find that balneotherapy-induced changes in uricemia and uricosuria determine changes in immune status by 60%. Conclusion. Endogenous uric acid has a modulating effects on a number of immune parameters in patients with neuroendocrine-immune complex dysfunction on background of chronic inflammatory diseases.